From Archipelago to Pandemic Battleground: Unveiling Indonesia's COVID-19 Crisis - Biyan Nathanael Harapan; Triswan Harapan; Lenny Theodora; Nadia Ayurini Anantama (Springer, 2023)
Abstract The coronavirus disease 2019 (COVID-19) pandemic has posed unprecedented challenges to countries worldwide, including Indonesia. With its unique archipelagic geography consisting of more than 17,000 thousand islands, Indonesia faces unique complexities in managing the spread of the virus. Based on existing literature, this review article elaborates on key issues that have shaped Indonesia's COVID-19 response. The article begins by examining the early stages of the COVID-19 pandemic in Indonesia, along with the implementation of various preventive measures and the impact of the virus on public health. This article examines how Indonesia's socio-economic factors have generally influenced its healthcare system and further delves into the COVID-19 response strategies implemented by the Indonesian government and public health authorities as well as overall crisis preparedness. It discusses the actions taken to control the spread of the virus, including testing strategies and vaccination efforts. The difficulties encountered in implementing these measures are presented. In conclusion, this review article provides a comprehensive understanding of the COVID-19 crisis in Indonesia, covering facts on multiple dimensions ranging from the timeline of the pandemic to vaccination efforts, epidemiology, socio-economic implications, testing strategies, mobility patterns, public holidays, the impact of working from home, and the utilization of complementary and alternative medicine in addition to the standard of care for COVID-19. The insights gained from this article can complement future strategies for pandemic management and response in Indonesia and other countries facing similar challenges.